2020
DOI: 10.1029/2020gl090857
|View full text |Cite
|
Sign up to set email alerts
|

Interplanetary Shock Impact Angles Control Magnetospheric ULF Wave Activity: Wave Amplitude, Frequency, and Power Spectra

Abstract: We present the first clear observational connection between interplanetary shock impact angles and magnetospheric ultralow frequency (ULF) wave activity. We perform a comparative study of two solar wind shocks with relatively similar strengths, but one being nearly frontal and, the other, highly inclined. We utilize multipoint observations with magnetometers based in space and on the ground for comparisons. For satellites and ground stations occupying similar local time positions, we find that the ULF waves ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 76 publications
6
24
0
Order By: Relevance
“…By carefully analyzing two isolated substorms triggered by similarly strong shocks with very different inclinations, we found that the general geomagnetic activity represented by geomagnetic indices, energetic particle injection, auroral poleward expansion, westward auroral electrojet current, ground dB/dt variations, and ULF wave activity following the NFS were overall higher than the same effects following the HIS. These findings are supported by many experimental (Oliveira et al, 2016(Oliveira et al, , 2020Oliveira & Raeder, 2015;Shi et al, 2019;Takeuchi et al, 2002;Wang et al, 2006) and simulation (Guo et al, 2005;Oliveira & Raeder, 2014;Samsonov, 2011;Samsonov et al, 2015;Selvakumaran et al, 2017) works in the literature.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…By carefully analyzing two isolated substorms triggered by similarly strong shocks with very different inclinations, we found that the general geomagnetic activity represented by geomagnetic indices, energetic particle injection, auroral poleward expansion, westward auroral electrojet current, ground dB/dt variations, and ULF wave activity following the NFS were overall higher than the same effects following the HIS. These findings are supported by many experimental (Oliveira et al, 2016(Oliveira et al, , 2020Oliveira & Raeder, 2015;Shi et al, 2019;Takeuchi et al, 2002;Wang et al, 2006) and simulation (Guo et al, 2005;Oliveira & Raeder, 2014;Samsonov, 2011;Samsonov et al, 2015;Selvakumaran et al, 2017) works in the literature.…”
Section: Discussionsupporting
confidence: 82%
“…Although the results of wave activity on 5 April 2010 seem to agree with the results reported by Ngwira et al (2018), the results observed during the 20 September 2015 are quite different. The later and weaker wave activity during the latter event are consistent with results showing that inclined shocks trigger less intense substorm activity (Oliveira & Raeder, 2014 and ULF wave activity (Oliveira et al, 2020) in comparison to shocks with small impact angles. Ultra-low frequency wave analyses with White Horse (WHIT) data for the nearly frontal shock (left column) and with Fort Simpson (FSIM) data for the highly inclined shock (right column).…”
Section: Magnetospheric Ulf Wave Contributions To Ground Db/dt Variationssupporting
confidence: 89%
“…Although the results of wave activity on 5 April 2010 seem to agree with the results reported by Ngwira et al (2018), the results observed during the 20 September 2015 are quite different. The later and weaker wave activity during the latter event are consistent with results showing that inclined shocks trigger less intense substorm activity (Oliveira & Raeder, 2014 and ULF wave activity (Oliveira et al, 2020) in comparison to shocks with small impact angles.…”
Section: Magnetospheric Ulf Wave Contributions To Ground Db/dt Variat...supporting
confidence: 89%
“…These periods are also marked on the bottom panel by the regions with enhanced ion energy flux represented by the first narrow region (single pulse) and the following two narrow regions (double pulse). Later, at 0640:21 UT, MMS definitely crossed the magnetopause boundary entering the magnetosheath, as is clearly shown by the polarity inversion of B z , increase in plasma density and decrease in plasma temperature, and enhanced ion energy fluxes, which are well-known magnetopause crossing signatures (e.g., Dong et al, 2018;Oliveira et al, 2020). Minimum variation analysis with the four MMS spacecraft yields θ xn = 137.67 • ± 2.2 • for the first structure, and θ xn = 143.74 • ± 0.53 • for the other two structures.…”
Section: Magnetospheric Ulf Wave Contributions To Ground Db/dt Variat...mentioning
confidence: 91%
See 1 more Smart Citation